2016
DOI: 10.1039/c6ra08536a
|View full text |Cite
|
Sign up to set email alerts
|

The microwave-assisted solvothermal synthesis of a novel β-ketoenamine-linked conjugated microporous polymer for supercapacitors

Abstract: A novel b-ketoenamine-linked conjugated microporous polymer (KECMP-1) was facilely synthesized with a high-throughput via Schiff base microwave-assisted condensation between 1,3,5-triformylphloroglucinol and m-phenylenediamine without a template or a metal catalyst. The resultant KECMP-1 shows an outstanding capacitance retaining ability (50% of the original 252 F g À1 at 1 A g À1 ) with the current density as high as 200 A g À1 , excellent cycling stability and long cycle life for energy storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 21 publications
(49 reference statements)
1
20
0
Order By: Relevance
“…20 CTFs can also be synthesized using microwaves via a ZnCl 2 salt-melt route. 108 Successful microwave-assisted synthesis using Suzuki coupling 109 and Schiff base reaction 110 have also been reported, requiring the same microwave heating temperatures as their solution-synthesized equivalents but within a shorter reaction time (2 h instead).…”
Section: Unconventional Synthesis Methods and Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…20 CTFs can also be synthesized using microwaves via a ZnCl 2 salt-melt route. 108 Successful microwave-assisted synthesis using Suzuki coupling 109 and Schiff base reaction 110 have also been reported, requiring the same microwave heating temperatures as their solution-synthesized equivalents but within a shorter reaction time (2 h instead).…”
Section: Unconventional Synthesis Methods and Compositesmentioning
confidence: 99%
“…In 2016, Wei et al reported the microwave synthesis of an amorphous βketoenamine-linked CMP (KECMP-1) for supercapacitors. 142 KECMP-1 was synthesized by a one-pot microwave-assisted Schiff-base condensation of m-phenylenediamine and 1,3,5triformylphloroglucinol at 150 °C for 2 h (Figure 22). KECMP-1 is microporous, with a surface area of 484 m 2 g −1 , and was shown to be chemically stable under various solvents including hexane, methanol, THF, o-DCB, DMF, water, 9 M HCl, or 9 M NaOH.…”
Section: Energy Storagementioning
confidence: 99%
“…are well established as an electrode material to store the high energy density with remarkable stability and outstanding performance [11][12][13][14]. Covalent organic framework (COF) [15][16][17][18] is a newly emerged class of crystalline organic framework with atomically well-defined pore aperture made from organic molecular assembly. Two-dimensional COFs are more advantageous over three-dimensional COFs because of inherent stacking behavior between two adjacent layers (π-π interaction),…”
Section: Introductionmentioning
confidence: 99%
“…Microwave‐assisted synthesis has been applied in the synthesis of CTFs, which is usually suitable for time‐ and energy‐efficient synthesis [44] . Microwave‐assisted synthesis using Suzuki coupling [88] and Schiff base reactions [89] has also been reported, with the same microwave heating temperature but shorter reaction time.…”
Section: Synthesis Of Porous Organic Polymersmentioning
confidence: 99%